Risk, Participation, and Performance Practice
XXIV, 264 p. 17 illus.
Keywords: This book explores a range of contemporary performance practices that engage spectators physically and emotionally through active engagement and critical involvement. It considers how risk has been re-configured, re-presented and re-packaged for new audiences with a thirst for performances that promote, encourage and embrace risky encounters in a variety of forms. The collection brings together established voices on performance and risk research and draws them into conversation with next generation academic-practitioners in a dynamic reappraisal of what it means to risk oneself through the act of making and participating in performance practice. It takes into account the work of other performance scholars for whom risk and precarity are central concerns, but seeks to move the debate forwards in response to a rapidly changing world where risk is higher on the political, economic and cultural agenda than ever before.